(untitled) (Sustainability in Debate, 2014)
Cattle ranch is of great importance on Central Brazil historical occupation and peasant forming. In the cerrados (savannas) of Norte de Minas region (Minas Gerais state), cattle is a central element of traditional peasant’s (called “Geraizeiros”) culture, economy, ecosystem management, way of life and territoriality. However, studies and debates about biodiversity conservation in the region, cattle still seems to be a “taboo”, as great impacts are related to it, despite the absence of studies that give real evidences or measures. In this article, I use references from literature to analyse the possibility of conciliation of traditional cattle ranch and biodiversity conservation in the Norte de Minas’ cerrados, suggesting a research agenda related to the theme.